2010
DOI: 10.1007/s10924-010-0229-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Recycling and Annealing on the Mechanical and Fracture Properties of Poly(Lactic Acid)

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 21 publications
3
43
0
2
Order By: Relevance
“…The first heating scans presented in Fig. 3 reveal that all the samples present a glass transition around 60 °C, followed by an endothermic peak related to the densification of the amorphous regions of PLA, that is, the physical aging of the polymer [20]. The samples also show a cold crystallization peak (T cc ) at approximately 110 °C and finally, a double peak melting endotherm (T m1 and T m2 ) near 150 °C.…”
Section: Effects Of Recycling Processes On the Structurementioning
confidence: 93%
See 1 more Smart Citation
“…The first heating scans presented in Fig. 3 reveal that all the samples present a glass transition around 60 °C, followed by an endothermic peak related to the densification of the amorphous regions of PLA, that is, the physical aging of the polymer [20]. The samples also show a cold crystallization peak (T cc ) at approximately 110 °C and finally, a double peak melting endotherm (T m1 and T m2 ) near 150 °C.…”
Section: Effects Of Recycling Processes On the Structurementioning
confidence: 93%
“…For instance, Scaffaro et al [17], Badía et al [18] and Żenkiewicz et al [19] reported that PLA presented reduced mechanical properties after 1, 5 and 10 reprocessing cycles. However, Nascimento et al [20] pointed out that a single reprocessing step does not significantly affect the structure, thermal and mechanical properties of PLA.…”
mentioning
confidence: 99%
“…The crystallinity of PLA has been found to increase consistently through annealing in most of the studies and the increase lead to an improvement in its heat resistance and overall mechanical performance. Park et al 90 and Nascimento et al 91 performed annealing of PLA under various conditions to obtain microstructures with different spherulite sizes and densities. The heat resistance of PLA was markedly improved when its crystallinity was increased by annealing.…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%
“…PLA is susceptible to thermo-degradation during melt processing operations [20,21]. For this purpose, the study of thermo-mechanical degradative phenomena associated to its re-processing [20,22,23] is of great concern in order to assess the possibility of recycling PLA-based nanocomposites. To enhance some properties of PLA, such as mechanical and gas barrier properties and to extend its use in food packaging applications, small amounts of nanoparticles can be loaded in the matrix [24].…”
Section: Introductionmentioning
confidence: 99%